Revisiting AMPylation through the lens of Fic enzymes. Issue 4 (April 2022) - Gulen, Burak; Itzen, Aymelt
Abstract : AMPylation, a post-translational modification (PTM) first discovered in the late 1960s, is catalyzed by adenosine monophosphate (AMP)-transferring enzymes. The observation that filamentation-induced-by-cyclic-AMP ( fic ) enzymes are associated with this unique PTM revealed that AMPylation plays a major role in hijacking of host signaling by pathogenic bacteria during infection. Studies over the past decade showed that AMPylation is conserved across all kingdoms of life and, outside their role in infection, also modulates cellular functions. Many aspects of AMPylation are yet to be uncovered. In this review we present the advancement in research on AMPylation and Fic enzymes as well as other distinct classes of enzymes that catalyze AMPylation. Highlights: Post-translational modifications (PTMs) of proteins are widely used not only in manipulating host signaling during bacterial infections but also in cellular homeostasis within eukaryotes and procaryotes. AMPylation [i.e., adenosine monophosphate (AMP) transfer to proteins] is a PTM that can be used by pathogenic bacteria for infiltrating the host and hijacking of the host cell machinery. AMPylation is carried out primarily by the large family of Fic enzymes as well as to a smaller extent by the DNA polymerase-β-like enzymes. Identification of AMPylation targets of host cells poses a major challenge; thus, the development of techniques is required for the characterization of yet unidentified cellular pathways affected by AMPylation. The recent discovery of the involvement of pseudokinases as a novel enzyme class catalyzing AMPylation may render this PTM more widespread than previously anticipated.